Synthetic DNA applications in information technology - Meiser, Linda C.; Nguyen, Bichlien; Chen, Yuan-Jyue; Nivala, Jeff; Strauss, Karin; Ceze, Luis; Grass, Robert N. (Nature Communications, 2022)
Synthetic DNA is a growing alternative to electronic-based technologies in fields such as data storage, product tagging, or signal processing. Its value lies in its characteristic attributes, namely Watson-Crick base pairing, array synthesis, sequencing, toehold displacement and polymerase chain reaction (PCR) capabilities. In this review, we provide an overview of the most prevalent applications of synthetic DNA that could shape the future of information technology. We emphasize the reasons why the biomolecule can be a valuable alternative for conventional electronic-based media, and give insights on where the DNA-analog technology stands with respect to its electronic counterparts.